ژیربێژیی و دانایی لە تەرازووی فەلسەفەی زماندا (چیرۆکی قورئانی خدری زیندە بە نمونە) - عەلی, بێستون ئەبوبەکر (Sulaimani Journal for Humanities, 2022)
This study is entitled (Philosophy and Wisdom in the Scale of Language Philosophy (The Qur'anic Story of Al-Khidr - ealayh alsalam - as a Model)), consists of two parts. The first part is provided for the relationship between language and philosophy especially the relationship between Kurdish language and philosophy, following the introduction of these concepts in a scientific way. In some occasions we have mentioned Iranian culture as an example of the eastern enlightenment comparing to the western culture; to support the Kurdish culture. These analyzes has been performed in linguistics’ framework, to perform our study objectively. The main purpose choosing this title is to clarify the philosophy of Kurdish language which rarely studied before. In the second part, a logical comparison has been performed between, the philosophical opinions of (Ludwig Wittgenstein (1889-1951)), and an example story (the story of Moses and Khidir) from the Holly Quran (18:60-82). The differences of their vison, wisdom and philosophy is discussed from their speech. This study could be a good phase towards further developed and more in-depth research in the field. Finally we have come to several scientific conclusions.